AN OVERVIEW OF CURRENT TAX REGULATIONS: IMPLICATIONS AND CHALLENGES - Hety Devita (Adisam Publisher, 2024)
Taxpayers can learn about current tax regulations by looking for relevant tax regulations. It is evident that taxpayers who are unaware of tax laws often turn into disobedient taxpayers. It is evident that taxpayers are more aware of the penalties they would face for failing to pay their taxes when they are more knowledgeable about tax legislation. Overall, taxes have a significant impact on the economy and business growth. However, the impact of taxes can vary depending on the type of tax, tax level, and fiscal policies implemented by the government. This article's methodology is library research that reveals theories about the issue under study. Based on easily accessible literature, an assessment of the ideas and concepts employed is done in this part. The role and significance of tax laws, their impact on financial management, their impact, and the difficulties in adjusting to changes in tax laws are all included in this research.